Chronic Alcohol Consumption Enhances Skeletal Muscle Wasting in Mice Bearing Cachectic Cancers: The Role of TNFα/Myostatin Axis. (11th November 2019) - Li, Yuanfei; Zhang, Faya; Modrak, Samantha; Little, Alex; Zhang, Hui
Abstract : Background: Chronic alcohol consumption enhances cancer‐associated cachexia, which is one of the major causes of decreased survival. The precise molecular mechanism of how alcohol consumption enhances cancer‐associated cachexia, especially skeletal muscle loss, remains to be elucidated. Methods: We used a mouse model of chronic alcohol consumption, in which 20% (w/v) alcohol was provided as sole drinking fluid, and Lewis lung carcinoma to study the underlying mechanisms. Results: We found that alcohol consumption up‐regulated the expression of MAFbx, MuRF‐1, and LC3 in skeletal muscle, suggesting that alcohol enhanced ubiquitin‐mediated proteolysis and LC3‐mediated autophagy. Alcohol consumption enhanced phosphorylation of Smad2/3, p38, and ERK and decreased the phosphorylation of FOXO1. These are the signaling molecules governing protein degradation pathways. Moreover, alcohol consumption slightly up‐regulated the expression of insulin receptor substrate‐1, did not affect phosphatidylinositol‐3 kinase, but decreased the phosphorylation of Akt and mammalian target of rapamycin (mTOR), and down‐regulated the expression of Raptor and p70 ribosomal kinase S6 kinase, suggesting that alcohol impaired protein synthesis signaling pathway in skeletal muscle of tumor‐bearing mice. Alcohol consumption enhanced the expression of myostatin in skeletal muscle, plasma, and tumor, but did not affect the expression of myostatin in non–tumor‐bearing mice. In TNFα knockout mice, the effects of alcohol‐enhanced expression of myostatin and protein degradation‐related signaling molecules, and decreased protein synthesis signaling in skeletal muscle were abolished. Consequently, alcohol consumption neither affected cancer‐associated cachexia nor decreased the survival of TNFα KO mice bearing cachectic cancer. Conclusions: Chronic alcohol consumption enhances cancer‐associated skeletal muscle loss through suppressing Akt/mTOR‐mediated protein synthesis pathway and enhancing protein degradation pathways. This process is initiated by TNFα and mediated by myostatin. Abstract : This study used a mouse model of chronic alcohol consumption and Lewis lung carcinoma to investigate the molecular mechanism of how chronic alcohol consumption enhances cancer‐associated cachexia, specifically skeletal muscle loss. We found that alcohol consumption‐enhanced skeletal muscle loss resulted from 1) impaired protein synthesis through suppressing Akt/mTOR signaling pathway, and 2) enhanced protein degradation through increasing LC3‐associated autophagy and enhancing MURF‐1/MAFbx‐mediated ubiquitin‐proteolysis signaling pathways. This process is initiated by TNFα and mediated by myostatin.